(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the author analyzes the process of guarantees of human rights. It is argued that the effectiveness and efficiency of legal guarantees depends primarily on the maturity of civil society institutions, the high level of legal culture of the population, the quality of work of law-making and law enforcement bodies, their officials.